EDUCATIONAL TRANSFORMATION: STRENGTHENING THE FOUNDATION OF DIGITAL INTELLIGENCE IN THE EDUCATION SYSTEM - Hosaini Hosaini; Robert Tetikay; Sulaiman; Al-Amin (Adisam Publisher, 2025)
Digital transformation has touched almost every aspect of life, including the education sector. The implementation of digital technology in learning opens up new opportunities to create a more adaptive and inclusive educational environment. This study aims to explore the impact of digital transformation on education, focusing on accessibility, personalization of learning, and skills development for the 21st century. The research method used in this study is the literature research method. The results show that access to education is significantly improved by digital learning resources, especially for individuals in remote areas and those facing economic barriers. Personalization of learning through data analytics and AI shows improvement in learning motivation and retention of material, resulting in more effective learning outputs. Furthermore, the introduction to digital technologies in the learning process has prepared students with skills essential for success in the modern workplace, including virtual collaboration, critical thinking, and problem-solving.